Improving Sales by Object-Oriented System Approach: E-Commerce Utilization Analysis - Aman, Mustar; Sasono, Ipang; Nugroho, Yunianto Agung; Riyanto; Suroso (International Journal of Social and Management Studies, 2021)
The development of Micro, Small, and Medium enterprises from year to year is influenced by the use of Information Technology and Information Systems. E-commerce is a technology that supports the development of Micro, Small, and Medium enterprises today. DM Khasanashop is a boutique company that sells a wide variety of clothes and pants from the lowest prices to the highest prices. Based on the results of the analysis carried out at DM Khasanashop Tangerang, the researcher can conclude that the problem that occurs in the sales system at DM Khasanashop is that sales have not been web-based or e-commerce and the data management system has not been computerized because the data processing process is still conventional and promotional media, still use brochures, banners, and business cards. The research objective was to determine the sales system using conceptual analysis and to determine the supporting and inhibiting factors in Khasanashop DM. The research method used is descriptive qualitative. Data collection techniques were carried out utilizing observation, interviews, and literature study. The results of this research show that management can be seen in several processes, namely making details of product prices, managing order data, employees packing products to sending products to consumers.